Quality of life at work for nurses in the 112 and 061 emergency healthcare systems in Spain - Beatriz Ruiz-Antón; Rodrigo Martínez Quíntana (Colegio de Enfermería de Caceres, 2017)
Introduction: A high-quality professional life is associated with increased motivation and the ability to adapt to constant change. Objective: To enhance our knowledge concerning the quality of professional life as perceived by nurses in the emergency healthcare systems in Spain. Methods: The study population included 2,852 professionals, and we obtained 328 (11.5%) valid responses. The data indicate that 80% of respondents had been in their position for more than 10 years. The study used the specifically validated questionnaire CVP-35, which examines quality of life at work. Results: The global quality of life score was approximately 6.76 points. The highest scoring item was "My work is important for the lives of other people" (9.12), and the lowest score was "Possibility of promotion" (3.76). The evaluation of the various dimensions was heterogeneous. The most significant correlations were found for 'management support' with 'intrinsic motivation' and for 'intrinsic motivation' with 'training'. The Spearman correlation coefficients were 0.521 and 0.439, respectively. There was a direct relationship between these score items. Conclusions: Nurses' perception of the global quality of professional life tends to be good, and the best results are found for 'intrinsic motivation' and 'training'. The worst areas were related to the items